Blow-Up of Solution of Lam Wave Equation with Fractional Damping and Logarithmic Nonlinearity Source Terms - Benramdane A.; Mezouar N.; Bensaber F.; Boulaaras S.; Jan R. (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
In this work, by the use of a semigroup theory approach, we provide a global solution for an initial boundary value problem of the wave equation with logarithmic nonlinear source terms and fractional boundary dissipation. In addition to this, we establish a blow-up result for the solution under the condition of non-positive initial energy. 2023 by the authors.